Reflections on the Significance of Images in Genocide Studies: Some Methodological Considerations - Sánchez-Biosca, Vicente (Genocide studies and prevention, 2018)
Social practices such as massacres, mass violence and the extermination of entire populations are not a historical novelty. Indeed, when Raphael Lemkin coined the term genocide in 1944 he was but giving a new name to an old crime.1 Such phenomena have been witnessed by humanity since Ancient times and historians, as well as artists and writers, have utilized every tool at their disposal to find ways to depict them and impress upon their audience the impact they had. Insofar as these are extreme phenomena that challenge the very notion of our humanity, such events inevitably test as well the limits of representation. Eyewitness accounts, historical narrations, philosophical observations, and ethical considerations, and studies from a social disciplines such as psychology, psychiatry, criminology, sociology and anthropology, have all been plagued with the difficulty posed by the comprehension and representation of genocides. As far as the visual is concerned, there has never been a lack of images attempting to depict or describe mass violence. Visual representation however, a form of representation that is adept at inciting emotions and affections, for this very reason, creates the ever-present risk of devolving into fascination, to the perversions of the gaze (voyeurism, in particular) and befuddlement of the conscience. Furthermore, as is to be expected, the disparity between the various ways of understanding, narrating and visualizing genocide and mass violence has produced complex configurations, especially since technological advances in photography allowed the visual capture of scenes as they transpired, introducing a literal notion of imprint